2004
DOI: 10.1037/0882-7974.19.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Fixation Patterns of High- and Low-Span Young and Older Adults: Down the Garden Path and Back Again.

Abstract: Abstract:Eye fixation patterns for older adults and young adults were monitored as they read sentences containing temporary syntactic ambiguities such as "The experienced soldiers warned about the dangers conducted the midnight raid." Young and older adults' fixation patterns were similar except that older adults made many more regressions to the Subject NP for ambiguous sentences. In a second experiment, high and low span older adults were compared to high and low young adults. First pass fixation times for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
101
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 26 publications
(96 reference statements)
16
101
2
4
Order By: Relevance
“…Since first pass fixations were similar for young and older adults, this pattern of results suggest that age-associated working memory limitations do not affect the initial interpretation of the cleft object and object relative clause sentences but the ability of older readers to resolve temporary ambiguities and misanalyses arising from conflicting syntactic, semantic, and pragmatic cues (Traxler, et al, 2005). Kemper et al (2004) found age group and span group differences in regressions and total fixation durations for reduced relative clause sentences containing temporary ambiguities. The cleft sentences and relative clause sentences used in the present experiment were unambiguous.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Since first pass fixations were similar for young and older adults, this pattern of results suggest that age-associated working memory limitations do not affect the initial interpretation of the cleft object and object relative clause sentences but the ability of older readers to resolve temporary ambiguities and misanalyses arising from conflicting syntactic, semantic, and pragmatic cues (Traxler, et al, 2005). Kemper et al (2004) found age group and span group differences in regressions and total fixation durations for reduced relative clause sentences containing temporary ambiguities. The cleft sentences and relative clause sentences used in the present experiment were unambiguous.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study by Kemper, Crow, and Kemtes (2004) using eye-tracking methodology reexamined these issues. Eye-tracking is a naturalistic task that imposes few restrictions on readers; they are free to skip words or phrases, read ahead and glance backwards, and re-read entire segments.…”
mentioning
confidence: 99%
“…For example, older adults have specific difficulty processing words and the syntactic and discourse levels of analysis during reading, and these differences may reflect more general age-related changes in working memory and attention (e.g., Kemper et al, 2004;Rayner et al, 2006;Stine-Morrow, Soederberg Miller, & Hertzog, 2006), or the use of strategies that compensate for these losses to maintain good comprehension. Poorer reading performance by older adults may also be inspired by substantial changes in vision that occur as a result of normal aging, including loss of high-contrast near-vision acuity and reductions in spatial frequency sensitivity (see, e.g., Derefelt, Lennerstrand, & Lundh, 1979;Elliott, Yang, & Whitaker, 1995;Owsley, Sekuler, Aging and Coordination of Binocular Fixations 12 Siemsen, 1983; for a review, see Owsley, 2011).…”
Section: 2009)mentioning
confidence: 99%
“…This conceptual frame, nevertheless, sets the stage for many points of disagreement on the particulars. Issues that are particularly controversial include (a) the processing mechanisms underlying lexical access and the instantiation of word meanings in particular contexts (Kambe, Rayner, & Duffy, 2001;Swinney, 1979), (b) the extent to which inferences are driven by attention to local or global coherence (Graesser, Singer, & Trabasso, 1994;McKoon & Ratcliff, 1992) (c) whether the availability of inferences reflect the automatic spread of activation or strategic integration (e.g., Long & Lea, 2005;van den Broek, Rapp, & Kendeou, 2005), and (d) more generally, the exact nature of the cognitive resources used to fuel computations (Caplan & Waters, 1999;DeDe, Caplan, Kemtes, & Waters, 2004;Just & Carpenter, 1992;Kemper, Crow, & Kemtes, 2004).…”
Section: The Nature Of Language Understanding From Written Textmentioning
confidence: 99%